Pengaruh Motivasi Berprestasi, Budaya Akademik dan Pengembangan Diri Terhadap Kinerja Dosen di Sekolah Tinggi Ilmu Tarbiyah Kabupaten Batu BaraA - Apner Nainggolan; Akrim Akrim; Indra Prasetia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of achievement motivation, academic culture, and self-development on the performance of lecturers at Tarbiyah College of Batu Bara Regency. The research sample was all lecturers at the Tarbiyah College of Batu Bara Regency, totaling 54 people. This study used a questionnaire for data collection. It was analyzed using multiple regression by conducting a simultaneous test, determination test, and partial test with a significant level of 5 percent (Î± = 0.05), which was processed with the help of the SPSS 22 tool. The study's results showed the influence of achievement motivation, academic culture, and self-development on lecturer performance. There is an influence of Achievement Motivation (X1), Academic Culture (X2), and Self-Development (X3) together on Lecturer Performance. The magnitude of the influence is indicated by the coefficient of determination R2 (R square) = 24.1, which means that Achievement Motivation (X1), Academic Culture (X2), and Self-Development (X3) jointly influence lecturer performance by 24.1% and other factors determine remaining 75.9%. In conclusion, there is a significant influence between achievement motivation, academic culture, and self-development on lecturer performance Keywords: achievement motivation, academic culture, lecturer performance, self-development